Facial injuries in children and adolescents victims of aggression (Research, Society and Development, 2021)
Child maltreatment may occur as the intentional use of power, effective or attempted, against children under 18 years old, that results or may result in actual or potential harm. It affects a vulnerable population, causing physical and/or emotional consequences persisting throughout their lives. This study aimed to characterize episodes of child maltreatment, with focus on facial injuries, in a Brazilian city (Teresina, PI). This is a retrospective study with a quantitative approach, carried out in the database at the Institute of Forensic Medicine in Teresina, between the years 2017 and 2019. All reports of bodily injury of children from 0 to 18 years were collected and statistically analyzed (SPSS 22.0). During the period analysis, 811 reports of bodily injury were identified. There was a predominance of female victims aged between 12 and 18 years old, the involvement of men with some family relationship with the victim was highly associated. Facial injuries represented 35.8% of the whole sample and 98.6% of those found in the head and neck region (41,6% of the total). The orbital (29.0%) was the most affected site, followed by the frontal (25.9%), malar (23.4%), labial (17.6%) and cheek area (11.4%). There is a high prevalence of injuries to the head and neck region, this fact emphasizes the importance of a trained professional, especially a dental surgeon, in the analysis and interpretation of these injuries during forensic examination.